A Scalable Emulator for Quantum Fourier Transform Using Multiple-FPGAs With High-Bandwidth-Memory - Hasitha Muthumala Waidyasooriya; Hiroki Oshiyama; Yuya Kurebayashi; Masanori Hariyama; Masayuki Ohzeki (IEEE Access, 2022)
Quantum computing is regarded as the future of computing that hopefully provides exponentially large processing power compared to the conventional digital computing. However, current quantum computers do not have the capability to correct errors caused by environmental noise, so that it is difficult to run useful algorithms that require deep quantum circuits. Therefore, emulation of quantum circuits in digital computers is essential. However, emulation of large quantum circuits requires enormous amount of computations, and leads to a very large processing time. To reduce the processing time, we propose an FPGA emulator with high-bandwidth-memory to emulate quantum Fourier transform (QFT), which is a major part of many quantum algorithms. The proposed FPGA emulator is scalable in terms of both processing speed and the number of qubits, and extendable to multiple FPGAs. We performed QFT emulations up to 30 qubits using two FPGAs. According to the measured results, we have achieved $23.6 \sim 24.5$ times speed-up compared to a fully optimized 24-core CPU emulator.